Analisis Wacana Menurut Teori Theo van Leeuwen Tentang Topik Obat-Obatan Terlarang pada Surat Kabar Riau Pos - Mukhlis, Muhammad (GERAM, 2018)
This study entitled "Reading Comprehension Ability Class VIII students of SMP Nurul Falah Pekanbaru. The issues discussed in this research is how Ability Reading Comprehension Class VIII students of SMP Nurul Falah Pekanbaru. This study aimed to collect information and data on the ability of reading comprehension, then the data and information collected are described, analyzed and interpreted in detail and systematically in order to know the true picture. The population in this study were all eighth grade students totaling 150 students consisting of five classes. The sample used is a sample random sampling which took 50% of the population, then collected a sample of 75 students. The method used in this research is descriptive method, a method that exposes / decipher data. The theory used is the theory of Henry Guntur Tarin (2008), Abdul Razak (1991), and (2005), Kundharu Saddhono and Slamet (2012). Data analysis was performed after the data collected and processed is calculated using the formula proposed by Anas Sudijono (1987: 43), after a large percentage of students answer is known, then connected with the assessment criteria set out Burhan Nurgiantoro (2001: 400). The study concluded Reading Comprehension Ability Class VIII students of SMP Nurul Falah Pekanbaru in determining the basic idea is categorized quite ie 74.64%. Ability Reading Comprehension Class VIII students of SMP Nurul Falah Pekanbaru in determining the explanatory idea is categorized quite ie 70.13%. Ability Reading Comprehension Class VIII students of SMP Nurul Falah Pekanbaru in determining the mandate / view categorized enough that the author is 74.40%. Ability Reading Comprehension Class VIII students of SMP Nurul Falah Pekanbaru in determining which conclusions are categorized as being 64.00%. Overall concluded Reading Comprehension Ability Class VIII students of SMP Nurul Falah Pekanbaru is averaging 70.79% were categorized as adequate and acceptable hypothesis.